2019
DOI: 10.1002/andp.201900390
|View full text |Cite
|
Sign up to set email alerts
|

Effective Mass Enhancement and Thermal Conductivity Reduction for Improving the Thermoelectric Properties of Pseudo‐Binary Ge2Sb2Te5

Abstract: Ge 2 Sb 2 Te 5 is a famous phase-change memory material for rewriteable optical storage, which is widely applied in the information storage field. The stable trigonal phase of Ge 2 Sb 2 Te 5 shows potential as a thermoelectric material as well, due to its tunable electrical transport properties and low lattice thermal conductivity. In this work, the carrier concentration and effective mass of Ge 2 Sb 2 Te 5 are modulated by substituting Te with Se. Meanwhile, the thermal conductivity reduces from 2.48 W m −1 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
1
6
1
Order By: Relevance
“…It is seen that there is an increase in DOS for Se-alloyed sample near the Fermi level as compared with pristine Ge 2 Sb 2 Te 5 , which is consistent with the increased m d *. Similar phenomenon was observed in a very recent study [37]. Also, the mobility of Se-alloyed samples can be well modeled combining acoustic-phonon scattering and alloy scattering (Fig.…”
Section: Computationsupporting
confidence: 87%
See 1 more Smart Citation
“…It is seen that there is an increase in DOS for Se-alloyed sample near the Fermi level as compared with pristine Ge 2 Sb 2 Te 5 , which is consistent with the increased m d *. Similar phenomenon was observed in a very recent study [37]. Also, the mobility of Se-alloyed samples can be well modeled combining acoustic-phonon scattering and alloy scattering (Fig.…”
Section: Computationsupporting
confidence: 87%
“…Figure 6a shows the temperature dependence of the figure of merit (zT) for Ge 2 Sb 2 Te 5-x Se x and Ge 2 Sb 2-Te 5-y Se y samples. The pristine Ge 2 Sb 2 Te 5 displays a maximum zT value of 0.56 at 800 K. Owing to the increased power factor and reduced thermal conductivity, zT was enhanced to 0.71 and 0.74 in Ge 2 Sb 2 Te 3.9 Se 1.1 and Ge 2 Sb 2 Te 4.9 S 0.1 , respectively, about 30% enhancement as compared with pristine composition and also significantly higher than the result in previous study (zT = 0.41) [37]. Figure 6b presents the prediction of zT = S 2 p H el H T/ (Lp H el H T ?…”
Section: Computationcontrasting
confidence: 59%
“…As shown in Figure 8b, the zT max and zT ave of Ge 0.93 In 0.07 Sb 2 Te 4 single crystal in this work are much higher than the reported values in polycrystalline GST system (including GST124, GST225, and GST147) in the literature. [37][38][39][40][41] It should be noted that in a series of samples, the highest zT max and zT ave is not necessary to be obtained in the same sample, since the optimized carrier density for the highest zT max may be slightly different from that for the highest average zT. Here we got them in the same sample, which may be just because the optimized carrier concentration for them is pretty close, or the In-doping step we chose is too large.…”
Section: Dimensionless Figure Of Meritmentioning
confidence: 99%
“…[39] Du et al improved the TE performance of polycrystalline GST225 by substituting Te with Se. [40] Welzmiller et al reported that Cr doping in GST124 leads to a higher Seebeck coefficient, resulting in a peak zT of 0.3 at 723 K. [41] Recently, we reported a proof-of-principle atomic scale bottomup configurational entropy design in pristine GST124 single crystal, shedding light on the relation between configurational entropy and thermal conductivity. [42] Whereas, there is still no effective TE performance optimization reported for GST124 till now, and the origin for its low κ L has not been systematically investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…This same approach of band engineering was adopted by Tan et al [ 74 ] by alloying CdTe in n -type PbTe, resulting in a PF 3 times higher. Another technique utilising a similar concept is bandgap convergance [ 72 , 73 ]. Adding selenium (Se) to the TE material at a medium operating temperature raised the PF value.…”
Section: Advanced Approaches In Optimisation Of Zt Valuementioning
confidence: 99%